The Effect of Balanced Counseling Strategy and Audiovisual on Postpartum Mother's Interest in Using Postpartum Contraception at the Samboja Health Center - Mulyati; Dini Indo Virawati; Satriani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Postpartum contraceptive coverage rates are still low in both Indonesia and East Kalimantan. The coverage of postnatal family planning at the Samboja Health Center in 2022 is 43.2% and in 2021 it is 47.86%. Methods: This research method is a Quasi experimental design with a one group pretest and post test design. Results: Most of the mothers' interest in using postpartum contraception before being given a balanced counseling strategy along with audiovisuals had a low interest of 88.5%, after the intervention the respondents' interest increased to a high of 92.3% in postpartum mothers at the Samboja Health Center. Discussion: the use of audiovisual in the Balanced Counseling Strategy has the advantage that audiovisual can provide complete and easily accepted information so that it can encourage mothers' interest in using postpartum family planning. Conclusion: Balanced Counseling Strategy with Audiovisual in increasing postpartum women's interest in using postpartum contraception.